The Use of 1.5-Anhydroglucitol for Monitoring Glycemic Control in Islet Transplant Recipients - Eduardo Moraes Leao Peixoto; Nujen Colak Bozkurt; Shari Messinger; Maria Isabel Del Olmo García; Vincenzo Lauriola; Andrea Corrales; Eva Herrada; Camillo Ricordi; Rodolfo Alejandro M.D. (Cell Transplantation, 2014)
We evaluated whether 1,5-anhydroglucitol (1,5-AG) (GlycoMark ® ), a test for measuring postprandial glucose and glucose variability, could be a tool for assessing short-term glycemic control in islet cell transplant (ICT) subjects. Data of 21 subjects, with type 1 DM and allogenic islet transplantation, who had concomitant fructosamine, HbA1c, 1,5-AG ( n = 85 samples), and capillary glucose self-monitoring measurements ( n = 2,979) were analyzed retrospectively at different time points after ICT. A significant negative association was observed between 1,5-AG and HbA1c ( p = 0.02), but not with fructosamine. When HbA1c was divided in quartiles as <5.6, 5.6–5.9, 5.9–6.2, and >6.2, a decrease of an estimated 0.70 ± 0.30 μg/ml in 1,5-AG was associated with each quartile of increase in HbA1c ( p < 0.0001). There was a significant decline of 1.64 ± 0.3mg/dl in postprandial glucose values for each 1 unit increase in 1,5-AG ( p < 0.0001). For those with HbA1c ≥ 6.0% when 1,5-AG was ≥8.15 μg/ml, the mean estimated glucose level was 103.71 ± 3.66 mg/dl, whereas it was 132.12 ± 3.71 mg/ dl when 1,5-AG was <8.15 μg/ml. The glucose variability (Glu max - Glu min ) in subjects with 1,5-AG <8.15 μg/ml was 46.23 mg/dl greater than the subjects with 1,5-AG ≥8.15 μg/ml (HbA1c ≥ 6.0%). There was no significant association between GlycoMark and glucose variability where HbA1c < 6%. 1,5-AG significantly associated with postprandial glucose levels and glucose variability in ICT recipients with near-normal HbA1c (6.0–6.5%) levels. These findings suggest that 1,5-AG can be used to differentiate those ICT subjects with higher glucose variability despite having near-normal HbA1c. However, prospective studies are needed to evaluate the association between GlycoMark levels and the parameters of graft dysfunction/failure.